2011
DOI: 10.1007/s00436-011-2398-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Emodepside plus Toltrazuril Suspension (Procox® Oral Suspension for Dogs) against Prepatent and Patent Infection with Isospora canis and Isospora ohioensis-Complex in Dogs

Abstract: Three randomised, blinded and placebo-controlled laboratory studies were conducted to evaluate the efficacy of emodepside plus toltrazuril suspension (Procox(®) suspension for dogs) against Isospora canis and Isospora ohioensis-complex. Unweaned puppies were experimentally infected with sporulated oocysts of I. canis and/or I. ohioensis-complex. In each study, one group was treated during prepatency (2 or 4 days post infection) while dogs in the second group were treated individually after the onset of oocyst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Accessed March 13, 2017). Furthermore, ponazuril, an oxidized toltrazuril metabolite (toltrazuril sulfone), was investigated for antiprotozoal activity in horses, dogs, and cats (Altreuther, Gasda, Schroeder, et al., ; Furr, Quance, & Kennedy, ; Petry, Kruedewagen, Kampkoetter, & Krieger, ). Ponazuril (Marquis ® , Bayer Animal Health) and diclazuril (Protazil ® , Merck Animal Health) are currently indicated for use in horses for the treatment of equine protozoal myeloencephalitis (EPM).…”
Section: History Of Use Of Triazines In Veterinary Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…Accessed March 13, 2017). Furthermore, ponazuril, an oxidized toltrazuril metabolite (toltrazuril sulfone), was investigated for antiprotozoal activity in horses, dogs, and cats (Altreuther, Gasda, Schroeder, et al., ; Furr, Quance, & Kennedy, ; Petry, Kruedewagen, Kampkoetter, & Krieger, ). Ponazuril (Marquis ® , Bayer Animal Health) and diclazuril (Protazil ® , Merck Animal Health) are currently indicated for use in horses for the treatment of equine protozoal myeloencephalitis (EPM).…”
Section: History Of Use Of Triazines In Veterinary Medicinementioning
confidence: 99%
“…Moreover, successful treatment using a combined nematocide emodepside and toltrazuril (Procox ® ) during the prepatent period following experimentally induced coccidiosis (Isospora spp.) has been observed in dogs (Altreuther, Gasda, Schroeder, et al, 2011) and cats (Petry et al, 2011). In naturally occurring Isospora infections following both positive oocyst fecal shedding and during the suspected prepatent period, toltrazuril administration effectively reduced oocyst counts by >98% in dogs (Altreuther, Gasda, Adler, et al, 2011).…”
Section: Coccidiosismentioning
confidence: 99%
“…Similarly use of Sulfadimethoxine alone and in combination with ormetoprim has been proved effective in canines and felines (Wilkinson 1977;Dunbar and Foreyt 1985;Lindsay and Blagburn 1995). Administrations of emodepside plus toltrazuril suspension in combination with oral Amprolium have proven effectiveness against canine infection (Altreuther et al 2011). Anti-giardial drugs like metronidazole, tinidazole, quinacrine, and furazolidone have very limited effect but metronidazole has been reported successful in some cases (Trier et al 1974;Syrkis et al 1975;Butler and deBoer 1981;Hallak et al 1982;Forthal and Guest 1984;Weiss et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The major aim of the treatment includes reduction of clinical signs along with reduction in faecal oocysts for interrupting the life cycle (Daugschies et al 2000;Buehl et al 2006). Supportive therapies like fluid administration are done depending on the severity of clinical signs which can enhance the recovery of the animals (Altreuther et al 2011). It was concluded that the canine Isosporosis can be clinically managed by use of trimethoprime and sulphamethoxazole along with supportive therapies and metronidazole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation